A Case of Clozapine-Induced Myocarditis in a Young Patient with Bipolar Disorder - Ronny Cohen; Alla Lysenko; Thierry Mallet; Brooks Mirrer; Michael Gale; Pablo Loarte; Robert McCue (Case Reports in Cardiology)
We present a case of drug-induced myocarditis manifesting as acute heart failure in a young patient with bipolar disorder being treated for depression. The case describes a 20-year-old man being treated in the psychiatry ward for worsening depression when he started complaining of chest pain and shortness of breath. His list of medications included clozapine, lithium, lorazepam, and haloperidol. The main findings on physical examination were tachycardia, low-grade fever, crackles in both lung bases on auscultation, and the absence of any notable edema. Abnormal labs included a troponin of 0.9, with a CK of 245 and CK-MB of 3.1. An ECG revealed sinus tachycardia and left anterior fascicular block (LAFB). An echocardiogram revealed global hypokinesis, severe left ventricular dysfunction with an ejection fraction estimated at 20%. The patient had an admitting diagnosis of acute left ventricular systolic dysfunction likely secondary to drug-induced myocarditis (suspect clozapine) versus acute coronary syndrome. He was managed conservatively and transferred to another facility for endomyocardial biopsy confirming myocarditis. This case is an example of one of the most typical presentations of suspected drug-induced acute myocarditis and will hopefully prompt the reader to think of this underdiagnosed entity in the right clinical setting.